Studi Komparatif Tingkat Hiperaktif Pada Diet Gluten Free, Casein Free Anak Autis Di SLB Briliant Kota Batam - Elvi Murniasih; Utari Christya Wardhani; Egis Surya Septi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that has certain characteristics. One of them is the diagnosis of autistic comorbidity, namely Attention Deficit Hyperactivity Disorder (ADHD), nonpharmacological treatments are considered quite effective including dietary interventions. Hyperactive behavior in autistic children that has an impact in the form of difficulty in poor attention span to impulsiveness. Gluten free diet, casein free diet is recommended in the application of therapy in autistic people, this diet is one type of complementary therapy, which is carried out by regulating consumption patterns in autistic children. Objective: to determine the difference in the level of hyperactivity of autistic children between groups who apply gluten free, casein free diet with not applying gluten free, casein free diet. Method: comparative study by looking at the comparison between two groups with a total sampling technique of 20 people. Results: The level of hyperactivity in children on a gluten free diet, casein free as many as 9 (45%) respondents and 11 (55%) respondents did not do a gluten free diet, casein free obtained Mann Whitney U test results with a p-value of 0.027 where the p-value <0.05 or (0.027<0.05). Conclusion: Autistic children who apply a gluten free, casein free diet seem to have quite good attention than autistic children who do not apply a gluten free casein free diet. Suggestion: It is hoped that parents who have autistic children can adopt a gluten free diet, casein free as an alternative therapy.